PARADIPLOMASI LAMPUNG: Harapan dan Realitas - Hasbi Sidik (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2019)
The Lampung provincial government, in accordance with Lampung Province regulation No. 14 of 2013 concerning regional cooperation, can establish foreign cooperation. Provincial involvement in this international dimension has also been supported by the foreign cooperation guidelines issued by the Ministry of Foreign Affairs of Indonesia in 2006 and the Ministry of Home Affairs in 2008. Although the legal and technical provisions for implementation already exist, exploration of how regional foreign cooperation decisions are designed and taking into account the global-regional intersection dimension is an important matter that must be understood. Using a descriptive qualitative approach with interviews and literature methods, the primary and secondary data obtained were analyzed with the framework of the concept of regional foreign cooperation and paradiplomacy. The study shows that the initiation of paradiplomacy at the regional level has not been designed with the same understanding of the international and domestic dimensions. Although pioneering foreign cooperation has been carried out, the absence of policy integration has made the sustainability of these initiatives not very successful